Effect of organic fertilizer on the growth performance of Thyrsostachys siamensis (Buluh Siam) in Malaysia - Mohamed, Azmy; Ponnusamy, Parvin Anila; Ashaari, Zaidon; Sahri, Mohd Hamami; Mustafa, Zolkapli (Forestry Department Peninsular Malaysia, 2009)
Thyrsostachys siamensis is an important economic bamboo species in several Asean countries such as Thailand. It is worth to be exploited for shoot production in Malaysia too. This paper discusses the effects of organic fertilizer application on the growth of Thyrsostachys siamensis. The parameters observed were number of shoots, culm height and culm diameter at breast-height (dbh). Application of 4 kg and 6 kg rates of chicken dung gave a significant effect on the number of shoots and culm height. The potential of Thyrsostachys siamensis bamboo as a commercial species for shoot production is also discussed.